Mating-Induced Differential Expression in Genes Related to Reproduction and Immunity in Spodoptera litura (Lepidoptera: Noctuidae) Female Moths. Issue 1 (24th February 2020) - Gao, Bo; Song, Xiao-Qian; Yu, Hong; Fu, Da-Ying; Xu, Jin; Ye, Hui
Abstract: Mating promotes reproductive activity, which may impact immune performance. Paradoxically, mating frequently challenges females' immunity (e.g., infections). Therefore, studies of postmating resource allocation between reproduction and survival are likely to shed new light on life-history trade-off and sexual selection. Here, we used RNAseq to test whether and how mating affected mRNA expression in genes related to reproduction and immunity in Spodoptera litura female moths. Results show a divergent change in the differentially expressed genes (DEGs) between reproduction and immunity: the immune response was largely downregulated shortly after mating (~6 h postmating), which has some recovery at 24 h postmating; reproductive response is trivial shortly after mating (~6 h postmating), but it largely upregulated at 24 h postmating (e.g., egg maturation related genes were highly upregulated). Considering the fact that most of the total DEGs downregulated from 0 to 6 h postmating (from 51/68 to 214/260) but most of the total DEGs upregulated at 24 h postmating (816/928), it is possible that trade-offs between reproduction and immunity occurred in mated females. For example, they may shut down immunity to favor sperm storage and save limited resources to support the increased energy required in reproduction (e.g., egg maturation and oviposition). Mating-induced infections should be trivial due to low polyandry in S. litura . A reduced immune defense may have no threat to S. litura survival but may benefit reproduction significantly. Furthermore, obvious expression changes were detected in genes related to hormone production, suggesting that endocrine changes could play important roles in postmating responses.